Contenido de ADN, ARN y proteínas en diversos órganos de cobayos oriundos de la altura - Mamani A., Fernando (1999)
Measurement of DNA, RNA and proteins in guinea pig testes, spleen, kidney, heart, liver and lungs, expressed per 100g et tissue, per organ, and as number of cells per organ was performed in 9 male, adult guinea pigs native from high altitude (Morococha, 4540m) and in 10 male, adult guinea pigs native from sea level (Lima, 150 m).Body weight was lower in high altitude guinea pigs, though not significantly; however the weight of most organs was higher in high altitude guinea pigs.High altitude animals showed higher kidney and lung protein contents per 100g wet tissue and per organ. Heart showed higher protein content per organ. Livershowed lower protein content per 100g tissue, but lower content per organ.DNA content was higher in high altitude guinea pig testes, kidneys, heart and lungs. RNA content was increased in most organs of high altitude guinea pigs, except the spleen.Cell number was higher in high altitude guinea pig testes, kidneys, liver and lungs.